The Relevance of the Carnivalesque in the Québec Novel - Maroussia Ahmed (Studies in 20th & 21st Century Literature, 1984)
The Bakhtinian concept of space is topological rather than topographic, and encompasses the cosmic, the social and the corporeal; its function in the Québec novel consists in debasing the hierarchical verticality of Lent and of the "official feast." As Carnival is an anti-law,"law" in the Québec novel will be defined as the chronotope of the sacred space (the land or "terre" of Québec) in the genre known as the "novel of the land" ("le roman de Ia terre"). Until the Second World War, this chronotope transforms an Augustinian political view of the civitas dei into literary proselytism, via the ideology of agricultural messianism. Sanctification implies closure of space and of the text; the "outside" is debased, as is textual "difference," that is, carnivalesque writing as it appears, for example, in La Scouine by Albert Laberge or in Marie Calumet by Rodolphe Girard. During the 1940s, the "introspective novel" (Robert Charbonneau, Robert Elie, Robert Choquette) also connotes the "upper" euphorically and the "lower" dysphorically, but at this historical point as a function of the sanctification of the individual according to a Thomist hierarchy. The quest of the hero can be seen as the ascent of a vertical ladder of time/space/society/values. The novel of the 1960s takes on a carnivalesque air: former sacred spaces are diminished in number and importance or are debased; new spaces appear where the body communicates with other bodies and the world. The space of knowledge is not God, but the land. Novels of this period (by M.C. Blais, R. Carrier, A. Hébert) are constructed around two paradigms according to a Manichean view of the world, and bear a great predictability, thus leading to a new set of "upside down" cliches. The carnivalesque multiple is completely realized in Hubert Aquin's first two novels. Space ceases to bear meaning other than as a metaphor for horizontal kinetic writing. The text becomes the open space of a continuous game between narrator and reader. The importance given to the margin/marginality (the footnotes), the masquerade of characters and of polysemic words, the narrative games that deconstruct the medieval Aquinian world create the space of carnivalesque scriptural relativity. But Aquin also gives a political dimension to his carnivalesque writing: his position is that only a writing of chaos can correspond to a nation which is obsolete ("révolu") and imprisoned in stasis while still aspiring to a revolution. The mediation between stasis and movement is the text which acts as a detonator or pharmakon in the mind of the reader. The study of the carnivalesque in the Québec novel leads us to the discovery of an impressive number of heroes/writers/pharmakos/witches, all having the same kinetic transformatory function which is accomplished by the same medium: the word. They point to a society in transition during the 1960s and 1970s.
Keywords: Bakhtian space; cosmic; social space; space; corporeal space; Québec novel; Lent; official feast; carnival; law; terre; sacred space; le roman de la terre; novel of the land; messianic; sanctification; La Scouine; Alnert Laberge; Marie Calumet; Rodolphe Girard; Robert Charbonneau; Robert Elie; Robert Choquette; Thomist hierarchy; heroes; the word